Temporal trends in the search of information about HIV/AIDS in Spain - Sanz-Lorente, María; Sanz-Valero, Javier; Wanden-Berghe, Carmina (Revista Española de Comunicación en Salud, 2019)
Introduction: The use of health data from the Web has proven useful for evaluating various aspects of human behavior. Objective: to analyze the trend of searches for information on HIV/AIDS carried out in Spain, through Google. Methodology: Descriptive study. The data were obtained through online access to Google Trends, using the terms «HIV» and «AIDS». The variables were: related consultations; milestones; relative search volume (RSV) and temporal evolution. Consultation date 25 November 2018. Results: Users used search terms related to the main terms. There were three milestones in the results of search on «AIDS». The ratio between the two terms, 1.78 ± 0.13, presented significant differences (t = 5.29; p < 0.001). The RSV showed differences between the terms in the first time to study and the time course for ‘AIDS’ was clearly decreasing (R2 = 0.89, p < 0.001), while for ‘HIV’ was slightly increased (R2 = 0.02; p = 0,087). The relation of the RSV, between the two terms, for the entire period studied showed a low relation (R = 0.21, p = 0.005). Conclusions: the temporal evolution obtained is probably due to a change of social concern, from AIDS to HIV, or perhaps to a better understanding of the disease, which reflects the historical evolution of HIV and AIDS: the HIV infection as a chronic disease.
Keywords: Acquired Immunodeficiency Syndrome; HIV; AIDS; Access to Information; Google Trends